Accepting EU Private International Law Standards into the Legal System of Bosnia and Herzegovina: What Can be Done While Waiting for Godot? - Alihodžić, Jasmina; Meškić, Zlatan; Duraković, Anita (LeXonomica, 2019)
The process of accession of Bosnia and Herzegovina to the EU implies the introduction of EU standards on Private International Law into its internal legislation. This paper includes considerations related to the ways of implementation of the reform of private international law, having in mind the complex constitutional structure of Bosnia and Herzegovina, especially the division of competencies between the State and its entities. Bearing in mind the complexity of the decision-making process of different levels and the inability to reach political consensus on the reform, the article emphasises alternative mechanisms for introducing EU standards in the field of private international law into the legal system in Bosnia and Herzegovina. Given the external competence of the EU in its relations with third countries, this article gives a thorough analysis of the possibility of concluding international agreements in the field of private international law.